(untitled) (Research, Society and Development, 2021)
The aim of the study was to quantify and to map commercial food establishments and places for physical activity in a Brazilian Northeast capital, seeking to analyze the obesogenic food environment. A cartographic, cross-sectional survey was carried out by geocodification and geographic coordinates of food establishments and places for physical activity around the capital. The food establishments were classified according to their food supply and/or meal service, in conformity with the Dietary Guidelines for the Brazilian Population. The places for physical activity were categorized as public and private. The mapping was created by a Global Information System. Population density, income, and spatial distribution were analyzed according to the degree of agglomeration by administrative zones. 725 food establishments and 236 places for physical activity were identified, where 34.5% were classified as a healthy food establishment and 47.9% as public spaces for physical activity. Unhealthy food establishments are more present (27.4%) in the low population density areas and healthy establishments are more present (64%) in the high household income zone (p<0.01). The analyzed variables are clustered in the Central/South zone. It was concluded that the population is both exposed to an obesity-promoting environment, healthy food and places for physical activity. Strategies that encourage and facilitate healthy choices to protect individuals from unhealthy environmental factors and choices should be taken through public policies.